Picture and Picture Learning Model with Picture Card Media on Grade IV Students' Interest and Poetry Writing Skills - Ayu Agustin, Anis; Farida Nugrahani; Benedictus Sudiyana (Jurnal Elementaria Edukasia, 2024)
This study aims to investigate the effects of the picture and picture learning model on students' interest in and ability to write poetry. The approach is experimental research with a pretest-posttest control group design. The approach used in this study is quantitative. A cluster random selection method was employed to choose the research sample. This study's data gathering technique makes use of tests, observations, and documentation. The present study employed the t-test paired samples hypothesis test and prerequisite tests (homogeneity and normality tests) in its data analysis approach. With a t-value of 9.775 < a t-value of 1.706 and a p-value of 0.000 < 0.05, the findings indicated that students' interest in producing poetry grew by 20.77. Supporting this is the finding that using image cards for picture learning in grade IV of primary school influences pupils' motivation in creating poetry and validates Ha's findings. The student's skill score rose by 12.46, indicating that Ha was accepted and that using picture cards as a teaching method had an impact on pupils in grade IV primary school's ability to create poetry (t-value of 15.421 < t-value of 1.706 and p-value of 0.000 < 0.05). Thus, it can be said that grade IV students' attention and poetry writing skills are impacted by the image and Picture learning model using series image cards as a medium.